Epidemiology of mandibular fractures - frequency and trauma pattern comparison in seventies of twentieth century with modern times (2002-2012) - Król, Mateusz; Sieradzki, Paweł; Komisarek, Oskar (Journal of Education, Health and Sport, 2019)
Introduction: Mandibular fractures are a group of most common trauma with which maxillofacial surgeons have to deal in their clinical practice.Aim of the study: Analysis of mandibular fractures epidemiology in the group of patients treated in the Clinic of Maxillofacial Surgery at Poznan University of Medical Science between 2002 and 2012 and comparison of results with data from the period 1961-1974.Material and methods: Material consisted of medical documentation of patients treated in the Clinic of Maxillofacial Surgery in Poznan due to mandibular fractures between 2002 and 2012. 1990 patients experienced mandibular trauma but only 1701 cases were described precisely enough to take part in the analysis. The population of patients were divided by sex and age (16th year of life was the border of the divide). Using this data, the amount of single and multi-fragmental fractures, percentage distribution of fractures among anatomical structures of the mandible, frequency of fractures in age groups and seasons of the year were calculated. Then, results were compared with a publication about the epidemiology of mandibular fractures between 1961-1974.Results: The population of 1701 patients consisted of 1426 males, 235 females and 40 children up to 16 years old (25 boys and 15 girls). Male to female ratio was 6,13:1. Most fractures affected patients at an age between 20 and 30 years old, regardless of sex. On average, 199 hospitalization due to mandibular fractures a year had a place in a period of 2002-2012 (involving all cases). Most of the hospitalizations due to mandibular fractures occurred between April and September. From 2002 to 2012, 1864 anatomical structures were broken. Body (783), left angle (274), right condyle (241), left condyle (239) and right angle (195) were structures that were fractured most often. 895 (52,62%) cases were single fractures , 806 (47,38%) were multi-fragmental fractures. The greater the average amount of patients a year, the reduction of male to female ratio, single fractures to multi-fragmental fractures ratio is about 1:1, left angle in the group of most frequently fractured structures are the main differences between period 1961-1974 and 2002-2012.Conclusion: Analysis indicates that the epidemiology of mandibular fractures is a complex problem. Some elements are constant but other changes dynamically across time. In the opinion of abroad scientists, the development of technology, motorization, and changes in human behavior are the main reasons for such evolution.